Development and validation of a co-worker support scale for human resource practitioners at the workplace - Khairuddin, Khairun Nisa' (2019)
This study attempts to develop and validate an instrument of co-worker support among HR practitioners. The study employs a sequential exploratory mixed-method design to accurately define and develop the instrument. There were 3 phases in the study: Phase 1 was the conceptualisation of co-worker support which employed a qualitative approach involving in-depth interview sessions with 11 HR practitioners from various organizations in Malaysia. Based on these interviews, six dimensions of co-worker support were identified. The dimensions were labelled as ‘Assisting Co-worker’, ‘Providing Companionship’, ‘Protecting Co-worker’, ‘Guiding Co-worker’, ‘Recognizing Co-worker’ and ‘Respecting Co-worker’. Consistent with the relationship perspective in the Theory of Social Support (Lakey & Cohen, 2000), this finding helped to clarify the theory by providing specific examples of supportive behaviour at the workplace. Phase 2 was the development of co-worker support scale. Phase 3 was the validation of co-worker support scale which utilised a quantitative approach. Seven expert reviewers verified the validity and relevancy of the 89 items. Their concurrence supported the claim of content validity which was assessed using the Content Validity Index (CVI). The questionnaires were distributed to HR practitioners in the area of Klang Valley, Malaysia. Data were collected consecutively, and the initial data collection was for the Exploratory Factor Analysis, followed by the data collection for the Confirmatory Factor Analysis. The results of the EFA (n=201) and CFA (n=330) revealed that Co-worker Support (CWS) scale is multidimensional. Thus, the study confirmed the six dimensions of co-worker support that were identified in the conceptualisation stage in Phase 1. The dimensions met both discriminant validity and convergent validity, thus, fulfilling the criteria of construct validity. The reliability scores for each type of co-worker support were above .80. Based on the results, the instrument was proven to be valid and reliable. The Coworker Support (CWS) Scale can be used extensively. A clearer conceptualisation of the co-worker support established contributed to the body of knowledge. Practically, the CWS Scale can be used to assess potential support-related issues pertaining to co-worker support, which can help organizations undertake appropriate action to strengthen employee relations.